Nonscientific University Students Training in General Science Using an Active-Learning Merged Pedagogy: Gamification in a Flipped Classroom - Francisco Zamora-Polo; Mario Corrales-Serrano; Jesús Sánchez-Martín; Luis Espejo-Antúnez (MDPI AG, 2019)
Innovative teaching strategies are designing a new and promising landscape in education. They fill lessons with creativity and imagination for either the students or teachers. This article addresses an attempt to make the approach to science easier in a nonscientific environment: primary education at university level. Gamification methodologies were combined with a flipped classroom in order to free up in-class time and engage the students with the taught courses. A qualitative study was merged with quantitative measures of emotional and motivational parameters. These results were improved with four semistructured interviews. The results clearly showed a rise in the students' motivational levels, an acknowledgment of good teaching practices, and an evident enhancement of felt positive emotions toward science teaching and scientific issues.